The Percentage of Signet Ring Cells Is Inversely Related to Aggressive Behavior and Poor Prognosis in Mixed-Type Gastric Cancer - Marano, Luigi; Ambrosio, Maria Raffaella; Resca, Luca; Carbone, Ludovico; Carpineto Samorani, Osvaldo; Petrioli, Roberto; Savelli, Vinno; Costantini, Maurizio; Malaspina, Lara; Polom, Karol; Biviano, Ivano; Marrelli, Daniele; et al. (Frontiers in Oncology, 2022)
Background and objectives: Only recently the percentage of signet ring cells (SRC)s in gastric cancer (GC) has been proposed as an independent predictor of survival. High amounts of SRCs have been related to lower recurrence and mortality rates, better prognosis, and favorable clinicopathological features in poorly cohesive histotype. It is not known what the effect of SRCs percentage in mixed-type gastric cancer is. We investigate the role of SRCs as a prognostic marker in mixed histotype gastric cancer. Methods: A retrospective analysis was performed through a prospectively-maintained database of patients with diagnosed “mixed-type” gastric carcinoma, defined according to 2019 WHO classification. These patients underwent surgery between 1995 and 2016 and their tissue samples were stored in a tissue bank. All slides were analyzed, and patients were divided into three groups according to the percentage of signet ring cells: “Group 1” (displaying 10% of signet ring cells) “Group 2” (displaying <90% but >10% of signet ring cells), and “Group 3” (displaying 90% of signet ring cells). We compared clinical and pathological features as well as prognostic factors between the different groups. Results: Amongst 164 enrolled patients, 68.9% were male and 31.1% were female (p=0.612). The mean (SD) age at diagnosis was 71.49.6 years. Ninety-eight (59.7%) patients were classified as “Group 1”, 66 (40.3%) as “Group 2”, and none as “Group 3”. Five-year overall survival was remarkably higher in Group 2 (73.8%) in comparison to Group 1 (35.4%), p<0.001. Mortality risk was three times higher in patients with 10% SRCs pattern compared to those with 10% (HR 2.70 [95% CI 1.72-4.24]). After adjusting according to potential confounding factors, SRC percentage was still an independent predictor of survival. Conclusions: The proportion of SRCs is inversely related to aggressive behavior and poor prognosis in mixed-type gastric cancers, highlighting the role of SRCs amount as an independent predictor of survival.